2022
DOI: 10.1038/s42003-022-04065-6
|View full text |Cite
|
Sign up to set email alerts
|

Multiple mechanisms contribute to fluorometry signals from the voltage-gated proton channel

Abstract: Voltage-clamp fluorometry (VCF) supplies information about the conformational changes of voltage-gated proteins. Changes in the fluorescence intensity of the dye attached to a part of the protein that undergoes a conformational rearrangement upon the alteration of the membrane potential by electrodes constitute the signal. The VCF signal is generated by quenching and dequenching of the fluorescence as the dye traverses various local environments. Here we studied the VCF signal generation, using the Hv1 voltage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…In its conventional implementation, a cysteine substituted at a chosen site of interest is covalently labeled with a fluorophore and changes in the fluorophore’s microenvironment caused by direct or indirect conformational changes are reported as changes in fluorescence intensity resulting from collisional quenching or other mechanisms (e.g. (Cha and Bezanilla, 1998, Papp et al, 2022)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In its conventional implementation, a cysteine substituted at a chosen site of interest is covalently labeled with a fluorophore and changes in the fluorophore’s microenvironment caused by direct or indirect conformational changes are reported as changes in fluorescence intensity resulting from collisional quenching or other mechanisms (e.g. (Cha and Bezanilla, 1998, Papp et al, 2022)).…”
Section: Introductionmentioning
confidence: 99%
“…(Cha and Bezanilla, 1998, Mannuzzu and Isacoff, 2000)) and receptors (e.g. (Papp et al, 2022, Fryatt and Evans, 2014, Dekel et al, 2012)), has so far not been reported as a probe for VCF studies on spHCN channels. In this study, we show that in response to membrane hyperpolarization, ALEXA-488 fluorescence was consistent with a rapid movement of the S4 domain that preceded channel opening in agreement with previous studies (Bruening-Wright et al, 2007, Ramentol et al, 2020, Wu et al, 2023, Wu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, fluorescence-quenching amino acids neighboring the fluorophore have been accounted for generating the VCF signal as the major mechanism [3][4][5]. Introducing a dominant quencher (e.g., a tryptophan) near the fluorophore alters the VCF signal drastically [3,6]. Changes in the membrane potential during VCF measurements result in conformational changes in the voltage-sensitive protein, thereby changing the relative position of the quenching amino acids with respect to the attached fluorophore.…”
Section: Introductionmentioning
confidence: 99%
“…Other mechanisms have also been hypothesized to explain the formation of the VCF signal, such as movement of the fluorophore between less polar and aqueous environments [1,2,7], or the electrochromic effect [8][9][10]. Using the H V 1 proton channel as a tool, we recently provided evidence that the translocation of the fluorophore from the lipid membrane bilayer toward the aqueous phase extracellular solution during a conformational change is at least as necessary in VCF signal generation as the presence of neighboring quenching residues [6]. The VCF signal generated by quenching amino acids and the lipid environment can be described using a minimal 3-state model [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation